MARKETING PROMOTION STRATEGY @DENN MARKETT IN INCREASING THRIFTING PRODUCT SALES - Prastyo, Muhammad Fajar Dicky; Hariyanto, Didik (PT ANTIS INTERNATIONAL PUBLISHER, 2025)
Objective: This study investigates the marketing promotion strategies employed by @Denn Market to enhance sales of thrifting products in response to the growing fashion trend, focusing on the role of digital media in shaping consumer behavior. Method: Using a qualitative approach, the study utilized in-depth interviews and observations to analyze the effectiveness of promotional strategies through social media platforms, specifically Instagram and TikTok. Results: The findings reveal that @Denn Market’s use of viral marketing, influencer collaborations, and visually appealing content significantly boosted consumer engagement and sales. Additionally, these strategies helped strengthen brand image and customer trust. However, challenges such as government regulations on used clothing imports and negative consumer perceptions were identified as obstacles. Novelty: This study highlights the importance of creative and adaptive digital marketing strategies in maintaining the competitiveness of thrifting businesses. It contributes to understanding how digital promotion can drive sustainable growth in the fashion industry, offering insights for businesses navigating the evolving landscape of consumer behavior and market competition.